2009
DOI: 10.1111/j.1365-246x.2009.04333.x
|View full text |Cite
|
Sign up to set email alerts
|

Palaeomagnetism, rock magnetism and AMS of the Cabo Magmatic Province, NE Brazil, and the opening of South Atlantic

Abstract: S U M M A R YReconstruction of the South Atlantic opening has long been a matter of debate and several models have been proposed. One problem in tracing properly the Atlantic history arises from the existence of a long interval without geomagnetic reversals, the Cretaceous Normal Superchron, for which ages are difficult to assign. Palaeomagnetism may help in addressing this issue if high-quality palaeomagnetic poles are available for the two drifting continental blocks, and if precise absolute ages are availab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 54 publications
1
8
0
Order By: Relevance
“…This seems to also be corroborated by palaeomagnetic data (e.g. Font et al, 2009). Younger ages of ~90Ma (mostly K-Ar) have been noted in the Potiguar Basin (equatorial region) and as some ages from south of Brazil (Mizusaki et al, 2002;Souza et al, 2003).…”
Section: Accepted Manuscriptsupporting
confidence: 65%
“…This seems to also be corroborated by palaeomagnetic data (e.g. Font et al, 2009). Younger ages of ~90Ma (mostly K-Ar) have been noted in the Potiguar Basin (equatorial region) and as some ages from south of Brazil (Mizusaki et al, 2002;Souza et al, 2003).…”
Section: Accepted Manuscriptsupporting
confidence: 65%
“…(d) Mean Cretaceous paleomagnetic poles rotated into African coordinates compared to the global APWP. (e) Comparison with mean Cretaceous poles from Africa (compilation from Font et al [2009]). All representations are in the southern hemisphere.…”
Section: Discussionmentioning
confidence: 99%
“…One explanation for this is that, even if the GAPWP of Torsvik et al [2008] is considered as the most reliable model for paleomagnetic reconstructions, it is not free of error. To test for such scenario, we plotted a recent compilation of African poles gathered by Font et al [2009], which are only poles from igneous rocks, in order to minimize uncertainties in the paleomagnetic record of sedimentary rocks due to problems of inclination shallowing and time of magnetization acquisition. Figure 10e shows that despite their lower quality (i.e., large α 95 angles) in comparison to the Iberian poles, the African mean pole at 140 to110 Ma is in agreement with the GAPWP [ Torsvik et al , 2008].…”
Section: Discussionmentioning
confidence: 99%
“…According to some authors (e.g. Font et al, 2009;Font et al, 2014;Kruiver et al, 2001), the differences in B 1/2 and DP values can be interpreted as: varying degrees of oxidation of magnetite for component 1; different Ticontent in the Ti-poor magnetite for component 2; and different magnetic grain sizes for component 3. Sant'Ovaia (1993) in the Vila Pouca de Aguiar Pluton showed that the Vila Pouca de Aguiar and Pedras Salgadas granites have similar magnetic behavior.…”
Section: Magnetic Susceptibility and Isothermal Remanent Magnetizatiomentioning
confidence: 99%